Cycling to High School in Toronto, Ontario, Canada: Exploration of School Travel Patterns and Attitudes by Gender. Issue 1 (January 2015) - Wittmann, Katie; Savan, Beth; Ledsham, Trudy; Liu, George; Lay, Jennifer
This study surveyed attitudes, behaviors, social norms, and perceived control among the populations of students at three high schools in downtown Toronto, Ontario, Canada. The results showed a pattern of hesitancy to cycle on the part of female high school students compared with their male counterparts. Young women reported less access to a bicycle, less comfort or confidence in riding, more fear associated with cycling, and less ability to decide independently how to travel to school. The study identified two important variables that were likely associated with young women's smaller participation in cycling to school: overall cycling mode share and ability to decide their travel mode independently. The former variable tracked findings for the general population, and the latter appeared to have been associated with the proximity of immigration, as families might have brought associations of danger to independent female travelers from their countries of origin or perceived new dangers in Canada. While the former association is well established, the latter hypothesis warrants further research.